Potential Effects of Omega-3 Fatty Acids on Insulin Resistance and Lipid Profile in Maintenance Hemodialysis Patients: a Randomized Placebo-Controlled Trial (Iranian Journal of Kidney Diseases, 2016)
Introduction. Insulin resistance (IR), a risk factor for cardiovascular disease and all-cause mortality, is prevalent among maintenance hemodialysis patients. Effects of omega-3 fatty acids on IR in hemodialysis patients have not been well understood. This study aimed to determine the effects of omega-3 fatty acids on IR and serum lipids of hemodialysis patients. Materials and Methods. Fifty-four adult patients on hemodialysis were randomly assigned to receive either 1800 mg of omega-3 fatty acids or placebo daily for 4 months. Serum concentrations of glucose, triglyceride, total cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, C-reactive protein, insulin, leptin, and adiponectin were measured at baseline and after 4 months of the intervention. Insulin resistance was assessed using the homeostasis model assessment of insulin resistance and 2 adipokine-based measures of IR, including the leptin-adiponectin ratio and homeostasis model assessment corrected by adiponectin. Results. Mean differences of serum C-reactive protein, insulin, leptin, and adiponectin concentrations did not show significant difference between the two groups following 4 months of intervention. Fasting serum glucose and low-density lipoprotein cholesterol were not significantly influenced by omega-3 supplementation, either. Serum triglyceride, total cholesterol, and high-density lipoprotein cholesterol levels significantly decreased in the omega-3 group (P = .02, P = .03, and P < .001, respectively). None of the indirect indexes of IR showed significant changes at the end of the study in either the omega-3 or placebo group. Conclusions. Supplemental use of omega-3 fatty acids showed some beneficial effects on lipid profile of hemodialysis patients without any improvement in IR.